Analysis of Students’ Personality in Their Speaking Ability at Second Grade of SMPN 2 Parepare - Miftahul Jannah; Mujahidah; Ali Halidin (Institut Agama Islam Negeri Parepare, 2020)
The research aims is to how the students’ personality and do extrovert students get better speaking scores than introvert students in speaking ability. There are many students have basic in speaking because majority of the student study English in the course but some of student still lack speaking. One of the factors is from their personalities, such as self-confidence, nervous, and has personality extrovert and introvert. This study applies quantitative which employed descriptive quantitative research design. The data is started classifying students’ personality by using questionnaire and then the students’ speaking score by using test. The finding reveals that extrovert students get better speaking score than introvert students in speaking ability. In addition, the result of students’ speaking test showed that from the basic of determine the result by Mann Whitney This showed the Asymp.Sig> 0,05 so hypothesis accepted it can answer this second research question, which is to know do the extrovert students get better speaking score than introvert students in speaking ability.